Strain improvement for enhanced erythritol production by Moniliella pollinis Mutant-58 using jaggery as a cost-effective substrate - Khatape, Anil B.; Rangaswamy, Vidhya; Dastager, Syed G. (International Microbiology, 2024)
Erythritol has been produced by various microorganisms including Yarrowia, Moniliella, Aureobasidium, and Candida strains. Due to its relatively high price, erythritol sweetener is used lesser than other polyols despite having many advantages. Therefore, in this study, Moniliella pollinis strain was improved for erythritol production by chemical mutagenesis and subsequently screening for cost-effective carbon sources for the enhanced erythritol yield. M. pollinis was subjected to N-methyl N-nitro N-nitroso guanidine (NTG), ethyl methyl sulfonate (EMS), and UV mutagenesis for improved erythritol production. The fmutant strains were evaluated for enhanced erythritol production medium optimization by using different carbon substrates at the shake flask level. To enhance the production of erythritol and statistical media, optimization was carried out using a central composite design (CCD). Among 198 isolated mutants, Mutant-58 strain generated by EMS mutagenesis was selected for further assessment. The Mutant-58 strain showed significant morphological changes as compared to the parent strain. Furthermore, statistically optimized media composition resulted in the higher production of erythritol (91.2 & PLUSMN; 3.4 g/L) with a yield of 40.7 & PLUSMN; 3.4 % in shake flask experiments. The optimized medium composition for erythritol production constitutes (g/L) 225 jaggery, 4.4 yeast extract (YE), 4.4 KH2PO4, 0.31 MgSO4, and pH 5.5. The present study demonstrated strain improvement, media, and process optimization resulting in a 30% increase in the erythritol production in the Mutant-58 as compared to the parent strain. This is also the first instance where jaggery has been used as a cost-effective carbon source alternative to glucose for industrial-scale erythritol production.
Keywords: Erythritol; Fermentation; Moniliella pollinis; Mutation; Optimization; renewable resource